Global equity gauge alliance: reflections on early experiences - McCoy, David C. (2003)
The paper traces the evolution and working of the Global Equity Gauge Alliance (GEGA) and its efforts to promote health equity. GEGA places health equity squarely within a larger framework of social justice, linking findings on socioeconomic and health inequalities with differentials in power, wealth, and prestige in society. The Alliance's 11 country-level partners, called Equity Gauges, share a common action-based vision and framework called the Equity Gauge Strategy. An Equity Gauge seeks to reduce health inequities through three broad spheres of action, referred to as the 'pillars' of the Equity Gauge Strategy, which define a set of interconnected and overlapping actions. Measuring and tracking the inequalities and interpreting their ethical import are pursued through the Assessment and Monitoring pillar. This information provides an evidence base that can be used in strategic ways for influencing policy-makers through actions in the Advocacy pillar and for supporting grassroots groups and civil society through actions in the Community Empowerment pillar. The paper provides examples of strategies for promoting pro-equity policy and social change and reviews experiences and lessons, both in terms of technical success of interventions and in relation to the conceptual development and refinement of the Equity Gauge Strategy and overall direction of the Alliance. To become most effective in furthering health equity at both national and global levels, the Alliance must now reach out to and involve a wider range of organizations, groups, and actors at both national and international levels. Sustainability of this promising experiment depends, in part, on adequate resources but also on the ability to attract and develop talented leadership.